Educação Física escolar: implicações das políticas educacionais na organização do trabalho pedagógico. - Baccin, Eclea Vanessa Canei (2010)
The aim of this paper is to analyze the implications of educational policies of the state of Rio Grande do Sul (managed 2007-2010) in the organization of educational work in the discipline of physical education a state school in Pelotas, from the relationship between the broader policy orientations and actions defined by the state government. For this challenge, we base on the theory of dialectical historical materialism that gives us the tools of thinking to grasp the multiple determinations of reality. The techniques and research procedures used to collect data were semi-structured interviews and observation of lessons. All the situations experienced in school were recorded in a diary. In interpreting the data we used the content analysis. Participated in the research field of three physical education teachers, the director and educational coordinator of a state school. To achieve this goal, we seek at first to trace the relations between labor and capital that determine policies and educational reforms in Brazil. Then try to identify the assumptions of national education policies and those proposed by international agencies like the World Bank and IMF, and its relations with the current educational policies in the state. It was found that the educational policies implemented by this administration seek to balance the accounts of the state through tax adjustments that are directly influencing education. In the account of teachers there are numerous criticisms of this policy of cost containment that is causing the decline in quality of education and precariousness of the teacher's work. It is clear the quest for realization of a guided education in the guidelines of total quality, from the assessment tools as SAERS the attempted implementation of meritocracy and the withdrawal of rights historically achieved by the teachers. From the analysis of categories such as precariousness and intensification of teacher's work, education funding, teacher training, interdisciplinary and multidisciplinary, content and method, and objectives, and evaluation; we seek to explore the contradictions and possibilities present in pedagogical practice in order to demonstrate how is the organization of pedagogical work. For Physical Education was established that the contents are the predominant sports and that there is sidelined this course according to the new demands imposed by the labor market from the industrial structure and the requirement for new skills. Finally we demonstrate that the educational project management 2007-2010 is pivoted back to the interests of capital. All respondents demonstrated awareness of damage to education caused by current educational policies, and we have shown the strength of such workers, which is why many projects that management has not been performed.